Conflitos ambientais em unidades de conservação : uma abordagem sobre as relações de poder na institucionalização do Parque Nacional Serra de Itabaiana/SE - Brasil - Morales, Sheyla Pink Diaz (2011)
It is known that environmental conflicts bring along disputes over interests between several agents, by their social practices. Ergo, they re still set as the biggest managing challenge in preservation units. It is, in this dynamic of environmental conflicts in national parks, that the present paper permeated its researches and reflections. Thus, taking into consideration the complexity around the social relations and existing powers in preservation units and its relevance, the present research took as a study object the ISNP Itabaiana/SE - Brazil Sierra National Park. This object was chosen because of the need of this understood being, since its institutionalization is inserted in a complex force field. Under this assumption, the present paper had as its purpose to analyze and discuss the relations of power existent in the institutionalization of the ISNP. Documental researches were made in the main daily newspapers of the State of Sergipe, City Newspaper and Sergipe s Mail between the years 2003 and 2007. Through the documental research in the journalistic collection the reconstruction of the institutionalization of the ISNP was possible to be remade and to diagnose the main social factors involved in this creation process. The research by questionnaires and interviews with the main social players involved in the institutionalization of the INSP analyzed the political actions related to this process and identified the speeches that prevailed that moment. At the end, the paper was able to answer the raised questionings initially by the research: Which representations and speeches prevailed in the creation of the INSP? Which power relation patterns is the base of this action system? Who holds the Power in the definition and management of the environmental politics? Which resources base their actions? It was observed the importance of bourdieunians concepts about field, habitus, power and capital in the study of environmental conflicts in preservation units. The present study demonstrates that implantation of environmental public politics in Brazil still moves according to the politic interest, giving the creations of national parks a meaningful dispute field. This research becomes relevant by its pioneer feature in the study of the power relations applied to the preservation units contexts in the State of Sergipe.